Desenvolvimento do curso de gerenciamento em enfermagem on-line: experiência exitosa entre Brasil e Portugal - Prata, Ana Paula; Reis Santos, Margarida; Tronchin, Daisy Maria Rizatto; Peres, Heloisa Helena Ciqueto; Lima, Antônio Fernandes Costa; Alavarce, Débora Cristina; Aroldi, Juscilynne Barros da Costa (Escola de Enfermagem da USP, 2015)
Objective: To describe the experience of planning and developing online refresher courses in nursing management for nurses in the contexts of Brazil and Portugal. Method: The instructional design was based on meaningful learning theory, andragogy, and dialectical methodology, so it valued interaction between the actors, emphasizing the scenarios of practice and applying the concepts covered. The course structure is divided into nine theoretical units, four case studies, and an essay exam. Results: The course was positively evaluated by the participants, who reported opportunities for acquisition of new knowledge, interaction and exchange of experiences, motivation to study the topics, and self-learning. Conclusion: It is expected that description of this experience will stimulate proposals for new courses and programs in distance education modalities, improving the processes of teaching and learning so as to give support to future analyses
Keywords: Staff Development; Nursing Education; Distance Education; Nursing Informatics